Website-Based Kaveling Land Marketing Information System in Kampar Regency Planning - Dicky Wahyudi; Emon Azriadi; Safni Marwa (Journal of Engineering Science and Technology Management, 2021)
The land is one of the valuable assets of human life. In addition to beachheads, lthe and is also a place to make a living, set up houses and assets that can be traded at a high value. Acquiring land rights is usually done by transferring rights through buying and selling. Currently, the marketing of land that has been tiled (kaveling) for Kampar Regency is still using conventional means. The conventional way is to market the kaveling soil by word of mouth. In accordance with current technological developments, marketing is done by utilizing print media and social media such as Facebook and Instagram. This method is still ineffective. Aside from the limited range, the information displayed mixes with other sales information. To facilitate the reach and clarify the marketing information of kaveling land, it can be done by utilizing information technology and internet networks. So, information can be accessed by anyone, anytime and anywhere. The creation of a website-based kaveling land marketing information system in Kampar Regency aims to facilitate communication between sellers and buyers to interact with each other. The purpose of this research is to facilitate communication between sellers and buyers in marketing kaveling land through a website. The research method used in this study is the waterfall method. This waterfall method has a sequential flow of software starting from planning, analysis, design, implementation, testing and maintenance. This system is designed using Unified Modelling Language (UML).